Reporte de casos: Síndrome de inflamación multisistémica del adulto asociado a infección por SARS-CoV-2 - Laura Gilón-Córdoba (Asociación Colombiana de Infectología, 2023)
A few months after the COVID-19 pandemic began, an entity called inflammatory syndrome with multisystem involvement was described in children, whose main manifestations include fever, cardiac, neurological, gastrointestinal, and mucocutaneous involvement, associated with elevated acute-phase reactants. These ma-nifestations typically present a few weeks after infection. Later, in different parts of the world, cases in adults began to be published. Treatment is mainly aimed at modulating the immune response and associated hyperinflammation, with variable response and outcomes depending on the degree of multisystem involvement. We present two cases of adults treated at our institution.